Chapter 10: Electrochemical detection using ionic liquids - Silvester, Debbie; Aldous, L. (2016)
Ionic liquids are relatively new additions to the field of electrochemical sensing. Despite that, they have had a significant impact, and several major areas are covered herein. This includes the application of ionic liquids in the quantification of heavy metals, explosives, and chemical warfare agents, and in biosensors and bioanalysis. Also highlighted are the significant advantages ionic liquids inherently have with regards to gas sensors and carbon paste electrodes, by virtue of their non-volatility, inherent conductivity, and diversity of structure and function. Finally, their incorporation with carbon nanomaterials to form various gels, pastes, films, and printed electrodes is also highlighted.